STUDI INTERAKSI DAN PREDIKSI TOKSISITAS BEBERAPA KANDUNGAN SENYAWA DALAM PROPOLIS TERHADAP PROTEIN VIRUS SARS-COV DAN SARS-COV-2 SECARA IN SILICO - Febriani, Herliana
Two major epidemics in the past 20 years caused by CoV have occurred in humans, namely SARS and MERS. Both viruses infect the lower respiratory tract and cause severe respiratory syndrome in humans. In December 2019, a pneumonia case of unknown cause emerged in the city of Wuhan, China. The disease was then agreed with the name Covid-19. Corona Virus Disease (COVID-19) is an infectious disease caused by the Covid-19 virus. This virus belongs to the SARS (Severe Acute Respiratory Syndrome) family and is classified as SARS-CoV-2. A specific drug for the treatment of Covid-19 has not been found to date, some candidate compounds are still in preclinical or clinical trials. The development of natural ingredients can be an alternative for prevention and therapy for Covid-19. Propolis is reported to have antiviral and inhibitory effects on the ACE2, TMPRSS2 and PAK1 signaling pathways. This study aims to predict candidate compounds in propolis that can be used as SARS-CoV-2 virus inhibitors and predict their toxicity. The proteins used in this study were the main protease (Mpro) from the SARS-CoV virus (PDB ID: 2ZU5), SARS-CoV Papain-like protease (Plpro) (PDB ID: 4OW0) and Macrodomain SARSCoV-2 (NSP3). (PDB ID: 6WOJ). Candidate compounds were optimized using GaussView 5.0 and Gaussian 09W software. The docking method was validated by redocking the native ligand to the target protein structure, then the test compound was docked to the target protein by the validated method using AutoDock Tools 1.5.6. The docking results were then analyzed using the Discovery Studio Visualizer to determine the interaction of the test ligand with the amino acid residues on the target protein. The prediction of toxicity was carried out using the Toxtree and Vega programs. The compounds were predicted to be candidate inhibitors based on amino acid residues and bond energy are myricetin with a bond energy of -8.83 Kcal / mol in the SARS-CoV main protease (Mpro), pinocembrin with a bond energy of -5.58 Kcal / mol in SARS- CoV Papain-like protease (Plpro) and hesperetin with a bond energy of -7.29 Kcal / mol on Macrodomain SARS-CoV-2 (NSP3). The comparators used in this study were remdesivir, lopinavir, chloroquine, and hydroxychloroquine. The toxicity of myricetin, pinocembrin and quercetin was predicted to be low based on the Kroes TTC Decision Tree parameter and high based on the Cramer Rules parameter. Based on the prediction of toxicity using Vega, myricetin, quercetin and pinocembrin compounds were predicted to have moderate acute and chronic toxicity.